The smelly search - Stilton, Geronimo (Stilton, Geronimo. Cavemice, 2017)
Geronimo and his friends participate in a treasure hunt set up by his rival and are determined to overcome all of its challenging obstacles, including tricky riddles and smelly dinosaurs.